Waqafat Ma'a Kitab "Shifa' al-Ashwaq" li al-'Allamah al-Samhudi - Refaee, Hashem M. Yousif; Ali, Abdul Karim; Hj Abdullah, Luqman (Jurnal Fiqh, 2011)
This topic deals with those whose property contains unlawfulness and suspicious elements. Al-Samhudi in his book Shifa? al-Ashwaq bi Hukm ma Yakthur bay?uhu fi al-Aswaq concludes that transactions in the markets in which the unlawful elements are higher in percentage than the lawful ones are permissible. Obviously, it is difficult to understand this ruling, particularly when there are various hadiths that disregard such a transaction and earnings. This article is the first to examine the reasons why al-Samhudi preferred that ruling and second to compare al-Samhudi?s view with the view of other scholar?s so that we can reach a conclusion concerning this issue. It is found that the ruling regarding transactions where the wealth is mixed with prohibited wealth cannot be generalized as unlawful. It depends on the percentage of the mixture. However, in all cases to abstain from dealing with that kind of wealth and to on the pious side is the preferred path.